SOME PROBLEMS OF COMPUTER ASSISTED INSTRUCTION - Hunka, Steve (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1983)
Grasping the scope and consequences of change in the classroom signaled by the advent of the computer has become urgent for any thinking professional. It is easy to magnify the image of that change when the glass of the future is not clear. Hunka does not minimise the scale of changes impending, but as an experienced researcher into the underlying practical issues of educational enterprise he is able to bring to bear an instrumentality of certain considerations that gets us down to earth. After presenting us with an unexpected reminder of the richness of the state of the art in computer-assisted instruction that existed in 1968, he moves to current problems and poses a number of searching but answerable questions about such matters as the role of the teacher and the achievement of quality in instruction. His discussion of these problems, and his concluding part on problems yet to he resolved, is conducted with what one might call horse-sense systematically applied, in a manner that only research experience could supply but that gives teachers a firm grasp on concerns they can recognize as their own. The computer is thus brought into perspective in the landscape of the future. RÉSUMÉ Il est impératif aujourd'hui que tout professionnel averti comprenne la portée et les conséquences du changement amorcé par l'entrée de l'ordinateur à l'école. L'image que l'on se fait de ce changement se prête d'autant mieux au grossissement que la lunette que l'on pointe sur l'avenir est floue. Hunka ne minimise aucunement la portée des changements qui s'annoncent, mais en chercheur rompu à l'étude des questions pratiques qui soustendent l'entreprise pédagogique, il sait fair valoir un ensemble de considérations propres à nous ramener sur terre. Après le rappel de la richesse de l'enseignement assisté par ordinateur qu'il nous a présentée en 1968, Hunka passe aux problèmes actuels et soulève un certain nombre de questions difficiles mais résolubles, notamment sur le rôle du professeur et le bilan qualitatif de l'enseignement. Son exposé et sa conclusion sur les problèmes que restent à résoudre sont menés avec ce que l'on pourrait appeler du gros bon sens, d'une manière qui prouve son expérience de la recherche et qui permet aux professeurs de bien cerner certains problèmes qui leurs son propres. L'ordinateur est placé dans le contexte du paysage de l'avenir.